Business history - Wilson, J. F., author.
1 online resource.
Keywords: "The evolution of business history offers some radical ways forward for a discipline which is rich in potential. This shortform book offers an expert overview of how the field has relevance for contemporary business studies as well as the social sciences more broadly, as well as practitioners interested in historical perspectives. This book not only provides a comprehensive review of how the discipline of business history has evolved over the last century, but it also lays out an agenda for the next decade. Focusing specifically on the 'three pillars' of research, teaching and practical impact, the authors have outlined how while the first has flourished across many continents, the latter two are struggling to overcome significant challenges associated with how the discipline is perceived, especially in the social sciences. A solution is proposed that would involve academics working more closely with practitioners, thereby increasing the discipline's credibility across key stakeholders. The work here presented provides a concise and easily digestible overview of the topic which will be of interest to scholars, researchers and advanced students focusing on the evolution of business history and its impact on the way the world conducts business today"--